Myofibroblasts reside in the middle dermis of the keloids but do not predict the response to injection therapies: a double-blinded, randomized, controlled trial - Komulainen, Tuomas; Daymond, Patrik; Hietanen, Kristiina E.; Kaartinen, Ilkka S.; Järvinen, Tero A. H. (Frontiers in Medicine, 2024)
Introduction Keloids form as a pathological response to skin wound healing, and their etiopathology is poorly understood. Myofibroblasts, which are cells transformed from normal fibroblasts, are believed to contribute to pathological scar formation in wounds. Methods We carried out a double-blinded randomized controlled trial (RCT) comparing the efficacy of intralesional 5-fluorouracil (5-FU) and triamcinolone (TAC) injections in treating keloids. A total of 43 patients with 50 keloids were treated with either intralesional TAC or 5-FU injections, and their clinical response was evaluated. Biopsies were collected before, during, and after injection therapy from the active border of a keloid. To understand the role of myofibroblasts in keloids, we conducted an immunohistochemical analysis to identify myofibroblasts [α-smooth muscle actin (αSMA)] from the biopsies. We first defined the three histologically distinct regions-superficial, middle, and deep dermis-in each keloid. Results We then demonstrated that myofibroblasts almost exclusively exist in the middle dermis of the keloids as 80% of the cells in the middle dermis were αSMA positive. However, both the percentage of myofibroblasts as well as the area covered by them was substantially lower in the superficial and deep dermis than in the middle dermis of the keloids. Myofibroblasts do not predict the clinical response to intralesional injection therapies. There is no difference in the myofibroblast numbers in keloids or in the induced change in myofibroblasts between the responders and non-responders after treatment. Discussion This study demonstrates that myofibroblasts reside almost exclusively in the middle dermis layer of the keloids, but their numbers do not predict the clinical response to intralesional injection therapies in the RCT.